The inconclusive superiority debate of allogeneic versus autologous MSCs in treating patients with HFrEF: a systematic review and meta-analysis of RCTs - Omar T. F. Ahmed; Ziyad Tarek Ahmed; Abdulrahman W. Dairi; Maha Saad Zain Al-Abeden; Mohammed H. Alkahlot; Rana H. Alkahlot; Ghazi I. Al Jowf; Lars M. T. Eijssen; Khawaja Husnain Haider (Stem Cell Research & Therapy)
Abstract Background Recent randomized controlled trials have consistently demonstrated the safety and potential efficacy of MSC therapy for heart failure patients. This study delves into mesenchymal stem cells’ promising potential, offering a beacon of hope for the future of heart failure treatment with reduced ejection fraction (HFrEF). Methods We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for this systematic review and meta-analysis. We searched four databases and registers for RCTs, including PubMed, EBSCO, clinicaltrials.gov, ICTRP, and other relevant websites. We then selected thirteen RCTs with 1184 participants based on our pre-defined inclusion/exclusion criteria. Two independent assessors extracted the data and performed a quality assessment. The data were then plotted for various outcomes, including death, hospitalization, major adverse cardiac events, pump function parameters, and 6-min walk distance. Results The safety of MSC-based treatment has been consistently demonstrated with MSCs from autologous (AutoMSCs) and allogeneic (AlloMSCs) sources. This reassuring finding underscores the reliability of MSC-based therapy irrespective of their source. However, AutoMSCs showed a trend toward greater protective benefits. Subgroup analysis revealed no significant differences between AutoMSCs and AlloMSCs in improving LVEF; 0.86% (95% CI − 1.21–2.94%) for AlloMSCs versus 2.17% (− 0.48%; 95% CI − 1.33–5.67%) for AutoMSCs. AlloMSCs significantly reduced end-diastolic volume (LVEDV) by − 2.08 mL (95% CI − 3.52—0.64 mL). Only AlloMSCs significantly improved 6-min walking distance (6-MWD); 31.88 m (95% CI 5.03–58.74 m) for AlloMSCs versus 31.71 m (95% CI − 8.91–71.25 m) for AutoMSCs. The exclusion of studies using adipose-derived cells resulted in even better safety and a significant improvement in LVEF for AlloMSCs treatment. Conclusion Our findings suggest that AlloMSCs are at par with AutoMSCs in improving functional outcomes in heart failure patients. This underscores the need for future investigations in a larger patient cohort, emphasizing the urgency and importance of further research to fully understand the potential of MSCs in treating heart failure.